Exploring the Chemical Composition of Female Zucchini Flowers for Their Possible Use as Nutraceutical Ingredient - Luigi Castaldo; Sonia Lombardi; Luana Izzo; Alberto Ritieni (MDPI AG, 2023)
The zucchini (Cucurbita pepo L.) plant is well known for its fruits; however, its edible flowers appear to contain several active molecules, including polyphenols, which display poor bioaccessibility after gastrointestinal digestion (GiD). This study explores the bioaccessibility of polyphenols and antioxidant capacity within zucchini flower extracts during simulated GiD. Two nutraceutical formulations, non-acid-resistant (NAcR) and acid-resistant (AcR) capsules containing an aqueous extract of zucchini flowers, were employed in this investigation. Additionally, high-resolution mass spectrometry (Q-Orbitrap HRMS) was utilized for a comprehensive analysis of their polyphenolic constituents. Predominantly, rutin and isorhamnetin-3-rutinoside were the most prevalent compounds detected in the samples (514.62 and 318.59 mg/kg, respectively). Following in vitro GiD, the extract encapsulated in AcR capsules exhibited enhanced bioaccessibility during both the duodenal (189.2 and 162.5 mg GAE/100 g, respectively) and colonic stages (477.4 and 344.7 mg GAE/100 g, respectively) when compared with the extract encapsulated in NAcR capsules. This suggests that gastric acidity adversely impacted the release of polyphenols from NAcR capsules. In conclusion, the aqueous zucchini flower extract emerges as a promising and readily accessible source of dietary polyphenols. Moreover, the utilization of AcR capsules presents a potential nutraceutical formulation strategy to improve polyphenol bioaccessibility, enhancing its applicability in promoting health and well-being.